2021
DOI: 10.1001/jamanetworkopen.2021.0498
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Persistence of Cost-Related Medication Nonadherence Among Medicare Beneficiaries at High Risk of Hospitalization

Abstract: IMPORTANCE The unaffordability of drugs has been a persistent and elusive challenge in the US health care system. Little is known about the prevalence and persistence of cost-related medication nonadherence (CRN) in a population with high-cost, high-need resource utilization. OBJECTIVE To evaluate the prevalence and persistence of CRN among Medicare beneficiaries at high risk of hospitalization as well as the characteristics associated with CRN in this population. DESIGN, SETTING, AND PARTICIPANTS This cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 38 publications
(96 reference statements)
1
29
0
Order By: Relevance
“…More research is greatly needed to evaluate the adequacy of social policy to help the elderly cope with increasing demand for medications as they age. When CRN was examined longitudinally, one recent study suggested that younger age is a risk factor for persistent CRN 17. The evidence from this study corroborates the supposition that patients’ behaviour may evolve as they age.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…More research is greatly needed to evaluate the adequacy of social policy to help the elderly cope with increasing demand for medications as they age. When CRN was examined longitudinally, one recent study suggested that younger age is a risk factor for persistent CRN 17. The evidence from this study corroborates the supposition that patients’ behaviour may evolve as they age.…”
Section: Discussionsupporting
confidence: 82%
“…The GEE model uses a binomial family function, a probit link function, and an exchangeable correlation structure to address the binary outcome variable and correlation among the longitudinal follow-ups of the respondents. There is no particular order effect in the repeated measures in this analysis, as patients can report CRN intermittently, and the research has shown patients are not always persistent in CRN 17. In this analysis, the value of the age variable increases by 2 years for each respondent for each round of surveys from 2004 to 2014.…”
Section: Methodsmentioning
confidence: 94%
“…Our findings are consistent with a study of Medicare beneficiaries without cancer, where worse self-reported health was found in those reporting cost-related medication nonadherence compared with those adherent. 43 The increased risk for ED visits and hospitalizations after report of cost-related medication nonadherence may reflect difficulties in comorbidity management, since 69% of survivors in our study reporting cost-related medication nonadherence had at least one other noncancer comorbidity compared with 56% who did not report nonadherence. Tools such as those included in geriatric assessment could be an ideal provider-level intervention to guide comorbidity management in older cancer survivors and potentially improve medication adherence, improve health, and decrease costs.…”
Section: Discussionmentioning
confidence: 69%
“…We found that CRN was not associated with general health status and disability status for self-reported health outcomes. In comparison to other studies, De Avila et al reported a higher risk of persistent CRN was linked to worse self-reported health and depression (De Avila et al, 2021). Bambauer et al indicated that CRN was worsened by poor health among both older adults and beneficiaries with disabilities (Bambauer et al, 2007).…”
Section: Discussionmentioning
confidence: 92%